Pemeriksaan Kesehatan Siswa Kelas 3 dan Evaluasi Fasilitas UKS Sebagai Langkah Menuju Sekolah Sehat - Rezza Azis Dwi Ardiansyah; Fathir Abdil Rizal; Raka Satrya Dewanatara; Indra Saputra; Elias Bani Masan; Hilarius Bombang; Mashur Robbani; Rara Hamukti Kesit (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2025)
Regular student health checks and evaluation of School Health Unit (UKS) facilities are an important part of realizing a healthy school. This study aims to analyze the implementation of health checks for grade 3 students and evaluate the condition of UKS facilities at SDN Tanah Kali Kedinding V Surabaya. The method used is qualitative research with a phenomenological approach through in-depth interviews, observations, and documentation studies. The results of the study indicate that although UKS facilities are adequate, their implementation is not optimal. As many as 30% of students have visual impairments and another 30% have nutritional problems. The main causes are the lack of activity of UKS officers and the absence of an integrated examination schedule. It is recommended that schools reactivate the UKS function, train little doctors, and collaborate with health centers to support regular examination programs and ongoing health education. Thus, UKS can play a maximum role in supporting healthy and holistic student growth and development